Dynamique Urbaine Et Activités Informelles Comme Objet D’enseignement En Géographie Dans Les Classes De 2e Et 1e De Korhogo - Kouadio, Anne Marilyse; Séverin, Kouakou Kouassi (European Scientific Journal, ESJ, 2016)
The economy of African countries in their plurality is often characterized by traditional formal and informal dualism. In this study, we paid close observation to the following: almost everywhere in a semi underground or a total underground (Loukou, 2013), the renewal of the dynamism of the informal economy grouping according to the BIT (1993), the set of the unofficial little structured activities, and thus its difficulties which are quantifiable (small craftsmen, domestic service providers or not, small shopkeepers, etc.). In Ivory Coast as somewhere else in sub-Saharan Africa, this phenomenon occurs due to the badly mastered urbanization and the economic, social, and cultural crises stemming from austere politics of structural adjustment. The spatial and social reorganization of the Ivory Coast cities and his integration in the studies of the geography of Ivory Coast education system interpeeled us. To what extent does the knowledge relative to the interaction (urban dynamics/informal activities) establish an explicit object of teaching in the lessons of geography in a class of determination, strangely in the 2nd and 1st classes? This study is a scientific contribution for a better consideration of the current and ambient urban phenomena. It was conducted based on documentary and empirical data.